Determinants of QRIS Tap Usage: A Study of Jakarta Commuters - Fitri Alfiana; Corry Yohana; Sabo Hermawan (INDO PUBLISHING, 2026)
This study examines how perceived ease of use, perceived usefulness, and social influence affect the actual use of the QRIS Tap payment system on MRT Jakarta, with attitude toward using positioned as a mediating variable. An online survey was distributed to 162 respondents who had experience using QRIS Tap on MRT Jakarta, and the data were processed through Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4. The measurement model confirmed that every indicator met the required validity and reliability thresholds. The structural model showed that perceived ease of use, perceived usefulness, and social influence each had a positive and significant effect on attitude toward using, which in turn significantly influenced actual use. Mediation testing further confirmed that attitude toward using partially mediates the relationship between the three exogenous variables and actual use. These findings indicate that strengthening users' attitude is essential for sustaining the adoption of tap-based digital payment in public transportation, and the results provide practical input for MRT Jakarta and payment system providers in refining QRIS Tap services.